Outfoxed [large type] - Rosenfelt, David (Rosenfelt, David. Andy Carpenter novels., 2016)
Defense lawyer Andy Carpenter spends as much time as he can working on his true passion, the Tara Foundation, the dog rescue organization he runs. Lately, Andy has been especially involved in a county prison program where inmates help train dogs the Tara Foundation has rescued to make them more adoptable, benefiting both the dogs and the prisoners. One of the prisoners Andy has been working with is Brian Atkins, who has 18 months left on a 5-year term for fraud. Brian has been helping to train Boomer, an adorable fox terrier the Tara Foundation rescued from a neglectful owner. Brian and Boomer are clearly a terrific match. In fact, Andy hopes that Brian will adopt Boomer himself, once his sentence is up. But one day, Andy arrives at the prison to discover that Brian has used Boomer to make an ingenious escape, and man and dog are both in the wind. The next day, the man on whose testimony Brian was convicted is found murdered. Brian is caught and arrested for the crime, though he forcefully protests his innocence. Suddenly, Andy finds himself with a new client in Brian and a new dog in Boomer. And as he starts to dig deeper into the murder and the events leading up to it, Andy realizes he might be putting them all in far more danger than anyone had realized.